2021
DOI: 10.47197/retos.v44i0.88830
|View full text |Cite
|
Sign up to set email alerts
|

Estimulación temprana como programa neurológico en las capacidades y destrezas en niños en etapa infantil

Abstract: La estimulación temprana son técnicas educativas, empleadas en niños/as en etapa infantil (0-10 años) para corregir cognitiva, social y emocionalmente; trastornos psicomotrices para estimular capacidades compensadoras. El objetivo de la investigación es, demostrar la importancia de la estimulación temprana como respuesta ante la necesidad de emplear actividades educativas que le permitan al niño/a contrarrestar habilidades y destrezas psicomotrices y lenguaje cognoscitivo, que coadyuve a una incorporación bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 2 publications
0
8
0
2
Order By: Relevance
“…The benefits of physical activity and sport in human beings are becoming more and more demonstrable thanks to the extensive literature on the subject. Many authors have shown that physical exercise is very positive at the motor, psychomotor, cognitive and socioemotional levels (Aguilar et al, 2021;Carretero-Martínez et al, 2014;Carretero-Martínez & Romero-Naranjo, 2015;Martínez et al, 2021;Pacheco et al, 2022;Padial-Ruz et al, 2022;Palma et al, 2021;Pérez et al, 2022;Romero et al, 2021;Rosa-Guillamón et al, 2021;Sayago-Martínez, et al, 2021;Zambrano et al, 2022). In the same way, studies have been carried out in which various parameters are analyzed in parallel to see if there is a relationship between them, such as physical activity and anxiety, memory or calculation, finding very positive results (Luis-de Cos et al, 2019;Mezcua-Hidalgo et al, 2020;Villa et al, 2019).…”
Section: State Of the Questionmentioning
confidence: 99%
“…The benefits of physical activity and sport in human beings are becoming more and more demonstrable thanks to the extensive literature on the subject. Many authors have shown that physical exercise is very positive at the motor, psychomotor, cognitive and socioemotional levels (Aguilar et al, 2021;Carretero-Martínez et al, 2014;Carretero-Martínez & Romero-Naranjo, 2015;Martínez et al, 2021;Pacheco et al, 2022;Padial-Ruz et al, 2022;Palma et al, 2021;Pérez et al, 2022;Romero et al, 2021;Rosa-Guillamón et al, 2021;Sayago-Martínez, et al, 2021;Zambrano et al, 2022). In the same way, studies have been carried out in which various parameters are analyzed in parallel to see if there is a relationship between them, such as physical activity and anxiety, memory or calculation, finding very positive results (Luis-de Cos et al, 2019;Mezcua-Hidalgo et al, 2020;Villa et al, 2019).…”
Section: State Of the Questionmentioning
confidence: 99%
“…Existe un literatura abundante que demuestra que el ejercicio físico es muy positivo a nivel motor, psicomotriz, cognitivo o socioemocional (Aguilar et al, 2021;Martínez et al, 2021;Pacheco et al, 2022;Padial et al, 2022;Palma et al, 2021;Pérez et al, 2022;Zambrano et al, 2022). De la misma manera se ha realizado correlaciones de diversa índole muy positivas (Luis-de Cos et al, 2019;Mezcua-Hidalgo et al, 2020;Villa et al, 2019).…”
Section: Estado De La Cuestiónunclassified
“…The correct use of the body schema in Physical Activity and Sport Sciences brings wide benefits not only at a physical or cognitive level, but also at a socioemotional level (Aguilar et al, 2021;Carretero-Martínez et al, 2014;Carretero-Martínez & Romero-Naranjo, 2015;Martínez et al, 2021;Pacheco et al, 2022;Padial-Ruz et al, 2022;Palma et al, 2021;Pérez et al, 2022;Romero et al, 2021;Rosa al., 2021;Zambrano et al, 2022).…”
Section: Introductionmentioning
confidence: 99%